Recreation- and sport-led regeneration of urban water infrastructure - Book, Karin (Frontiers in Sports and Active Living, 2025)
Today, cities are to a growing extent looking for solutions for how urban infrastructure, like former industrial sites, can be developed into facilities for sport and recreation, as well as tourism. One example of such infrastructure is canals and former harbour areas. This paper aims at exploring the underlying factors behind, and the potential benefits and challenges of, recreation- and sport-led regeneration of urban water infrastructure with a focus on former harbours and canals, using three Scandinavian cities as examples: Copenhagen, Gothenburg and Malmö. A conceptual and theoretical frame is built around three perspectives: (1) contemporary trends and tendencies in sport and recreation, and spatial implications thereof, (2) urban regeneration, and (3) recreational spaces as ecosystem services. The empirical material is mainly based on six semi-structured interviews with informants involved in the planning, production and operation of the water infrastructure. As shown by the three examples, there are several benefits of a recreation- and sport-led regeneration of former harbours and canals. Those benefits include, for instance, ecosystem services, such as enhanced biodiversity and improved recreational opportunities, quality of life and well-being, as well as economic benefits in terms of tourism and positive attention. One of the examples also demonstrates that harbour regeneration could be an opportunity to develop methods for community participation and public-nonprofit partnerships. However, the examples highlight a number of challenges as well, such as polluted water and the technical issues and high costs involved in cleaning it; the provision of equal access to the water infrastructure; the creation of a safe co-existence for different actors and activities in the same water space; and diverse ownership, responsibility and regulation issues. To summarize, the paper shows that in a successful recreation-led regeneration of urban water infrastructure, the potential outcome is increased attractivity, activity and sustainability.